MAQASHID KOPERASI SYARIAH - Hadi, Nur (I-Economics, 2018)
Abstract The Islamic finance industry in the frame of Islamic financial institutions in the economy of a country plays a very important role, one of which is to assist businesses in carrying out, expanding, and developing their business activities through financing, among which are cooperatives that provide financing to cooperative members. Maqashid Koperasi sharia is a community-based business or business activity. His own philosophy is self-reliance, starting from the self and then to the independence of the group (people). Or vice versa, group independence that encourages individual independence in it. The resources gathered from members are a way to achieve economic sovereignty, so cooperating is actually a long-term business strategy that secures the business interests of each member from unfair competition. Cooperating is building a fortress from efforts to destroy and colonize large investors and more established business owners. Maqashid Sharia cooperatives at the level of religion are concentrations of power in driving out forbidden forms of muamalah and misleading ideologies. Riba is the prima donna of the business world, its existence is a direct derivative of the capitalist notion that puts money above everything else. Only solidarity is able to withstand the onslaught of expansion of capitalist business ventures, the institutionalized solidarity called cooperatives. Maqashid syirkah Islamic cooperatives contain six maqashid, as follows: 1). A large amount of capital is collected, so that it can be used to carry out large jobs too; 2) Can expedite the macroeconomic rate; 3). The creation of broader and more adequate employment opportunities; 4). The feeling of brotherhood between fellow capital holders and other partners; 5). Thought to advance the company becomes more because it comes from many people too; 6). Union transactions can generally be terminated or canceled. Keywords: Maqashid, Koperasi, Sharia. Abstrak Industri keuangan syariah dalam bingkai lembaga keuangan syariah dalam perekonomian suatu negara memegang peranan yang sangat penting, salah satunya membantu para pelaku usaha dalam menjalankan, memperluas, dan mengembangkan kegiatan usahanya melalui pemberian pembiayaan, diantranya adalah koperasi yang memberikan pembiayaan kepada para anggota koperasi. Maqashid Koperasi syariah adalah berjamaah dalam usaha atau kegiatan usaha yg berbasis komunitas. Filosofinya sendiri adalah kemandirian, mulai dari diri kemudian menjadi kemandirian kelompok (umat). Ataupun sebaliknya, kemandirian kelompok yang mendorong kemandirian individu didalamnya. Sumber daya yang terhimpun dari anggota adalah jalan bagi pencapaian kedaulatan ekonomi, sehingga berkoperasi sebetulnya adalah strategi usaha jangka panjang yang mengamankan kepentingan bisnis setiap anggota dari persaingan yang tidak sehat. Berkoperasi adalah membangun benteng dari upaya-upaya menghancurkan dan menjajah para pemodal besar dan pemilik usaha yang lebih mapan. Maqashid Koperasi syariah dalam tataran religi adalah pemusatan kekuatan dalam menghalau bentuk-bentuk muamalah yang terlarang dan ideologi yang menyesatkan. Riba itu primadona dunia usaha, keberadaannya adalah turunan langsung dari paham kapitalis yg mendudukkan uang diatas segalanya. Hanya solidaritas yg mampu menahan gempuran ekspansi usaha bisnis kapitalis, solidaritas yg melembaga itu namanya koperasi. Maqashid syirkah koperasi syariah mengandung enam maqashid, sebagai berikut : 1). Terkumpulnya modal dengan jumlah yang besar, sehingga dapat digunakan untuk mengadakan pekerjaan-pekerjaan besar pula; 2). Dapat memperlancar laju ekonomi makro; 3). Terciptanya lapangan pekerjaan yang lebih luas dan memadai; 4). Terjalinya rasa persaudaraan diantara sesama pemegang modal dan mitra kerja yang lain; 5). Pemikiran untuk memajukan perusahaan menjadi lebih banyak karena berasal dari banyak orang pula; 6). Transaksi perserikatan secara umum bisa berahir atau batal. Kata kunci: Maqashid, Koperasi, Syariah.